Answer :

Of course! Let’s work through the given problem step-by-step.

We are given the function [tex]\( f(x) = -x - 5 \)[/tex]. Our task is to find the value of this function when [tex]\( x = 0 \)[/tex].

Step-by-step solution:

1. Substitute [tex]\( x = 0 \)[/tex] into the function [tex]\( f(x) \)[/tex].

The function is defined as:
[tex]\[ f(x) = -x - 5 \][/tex]

2. Substitute [tex]\( 0 \)[/tex] for [tex]\( x \)[/tex] in the expression:
[tex]\[ f(0) = -(0) - 5 \][/tex]

3. Simplify the expression:
[tex]\[ f(0) = 0 - 5 \][/tex]

4. Therefore, we have:
[tex]\[ f(0) = -5 \][/tex]

So, the value of [tex]\( f(0) \)[/tex] is [tex]\( -5 \)[/tex].